The Oxford handbook of leadership and organizations - Day, David V. (Oxford library of psychology, 2014)
This title brings together a collection of comprehensive, state-of-the-science reviews and perspectives on the most pressing historical and contemporary leadership issues - with a particular focus on theory and research - and looks to the future of the field.